Advantages and disadvantages of online psychotherapy and decisions to use it in the era of the COVID-19 pandemic - analysis of mediation variables - Furmańska, Joanna; Rutkowska, Emilia; Lane, Håkan; Meixner, Johannes; Marques, Cristiana C.; Martins, Maria João (Frontiers in Psychiatry, 2025)
IntroductionIn recent years, online psychotherapy has gained importance as a flexible, cost-effective and widely available alternative to face-to-face therapy. Existing research suggests that psychotherapists see both the advantages and potential limitations of this form of work. It can be assumed that the perceived advantages and disadvantages of online therapy constitute the primary direct factors influencing decisions to adopt this form. However, in the era of the pandemic, it seems important to assess to what extent emotional factors - such as fear of infection or pandemic-related fatigue - and institutional factors - such as perceived infection rates or trust in the official recommendations, mediate this relationship. Therefore, this study aimed to examine how cognitive evaluations, accompanying emotions, and institutional conditions influenced psychotherapists’ decisions to adopt remote practice during the COVID-19 pandemic.Material and methodsThe study involved 283 psychotherapists from four European countries: Poland, Portugal, Germany and Sweden. An original interview created for the purposes of the study was used, to collect sociodemographic data related to the professional functioning of psychotherapists and aimed at learning about the advantages and disadvantages of online therapy in the opinion of psychotherapists. In addition, the Hospital Anxiety and Depression Scale (HADS), the Fear of Contracting COVID-19 Scale (FCS Covid-19), and the Pandemic Fatigue Scale (PFS) were used.ResultsThe results showed that the vast majority of therapists recognized both advantages (accessibility and convenience, health protection, flexibility, cost reduction and practicality, comfort and familiarity with the environment and functionality in online diagnosis and therapy) and disadvantages (problems with effectiveness, technical, safety and organizational difficulties) of online therapy. The analysis of the decision-making process showed no direct relationship between the perception of the advantages and disadvantages of online therapy and the decision to use it. Mediation analyses showed no indirect effects for advantages; for disadvantages, two institutional mediators operated in opposite directions (government recommendations: positive; society recommendations: negative), while emotional mediators were non-significant. This means that government recommendations and recommendations of psychotherapeutic societies mediate the relationship between perceived limitations and the decision to use online therapy.DiscussionThe results obtained make a significant contribution to the understanding of the advantages and limitations of online therapy perceived by psychotherapists and the factors directly and indirectly related to the decision to use it.